Serum alpha(2)-macroglobulin, transferrin, albumin, and IgG levels in preeclampsia - Horne, C. H. W. (1970)
A radial immunodiffusion technique has been used to measure levels of four serum proteins in preeclampsia with or without proteinuria and in normal pregnant and non-pregnant controls. In preeclampsia unaccompanied by proteinuria, albumin and transferrin levels are similar to those found in the normal pregnant controls, but there are significant falls in α(2)-macroglobulin and IgG. When preeclampsia is accompanied by proteinuria there is a marked fall in albumin and an increase in α(2)-macroglobulin. Since α(2)-macroglobulin has antiplasmin activity it is possible that increased levels of this protein in preeclampsia accompanied by proteinuria contribute to the intravascular coagulation which has been described in this disorder.